Assessment of bond between asphalt layers - Muslich, Sutanto (2010)
Asphalt pavements are usually constructed in several layers and most of pavement design and evaluation techniques assume that adjacent asphalt layers are fully bonded together and no displacement is developed between them. However, full bonding is not always achieved and a number of pavement failures have been linked to poor bond condition